Serological cross reactivity among three species of tick - Ghos, S; Khan, M H (The Indian Journal of Animal Sciences, 2012)
In a multi-tick infestation. ddection of cross-reactive antigens between stages as well as species of ixodid ticks wilt facilitate both control strategy and epidemiology of the diseases, vectored by them. In repeated DID and ELISA tests. anti-BLAg sera exhibited antigenic cross-reactivity against all the antigens, prepared from all the stages of B. microplus, H. a. anatolicum and R. sanguineus. Present findings further revealed that the larval antigen of B. microphid may proviede cnadidate antigen for the control of these ticks.